Tuning ZnSe/CoSe in MOF-derived N-doped porous carbon/CNTs for high-performance lithium storage - Jin, Jun (2020)
Transition metal selenides with high theoretical capacities possess attractive potential as anode materials of lithium ion batteries (LIBs). However, the low electrical conductivity and structural collapse caused by the large volume change upon cycling always result in poor rate capability and rapid capacity fading. In this work, binary metal selenides (ZnSe/CoSe) encapsulated in N-doped carbon polyhedra interconnected with carbon nanotubes (denoted as ZCS@NC/CNTs) are prepared through a simple solution method, involving subsequent in situ pyrolysis and selenization of the metal–organic framework (MOF) precursor at moderate temperature. Such a rational ZCS@NC/CNTs hierarchical structure provides a stable interconnected conductive network, with porous structure and shortened pathway for charge transport, synergistically enhancing the Li+ insertion capability. This designed ZCS@NC/CNTs exhibits high capacity, excellent rate capability and superior cycling stability. Specifically, the synthesised ZCS@NC/CNTs demonstrates a high capacity of 873 mA h g−1 after 500 cycles at 0.5 A g−1. More importantly, a high stable capacity of 768 mA h g−1 can be retained after 1000 cycles even at a relatively high current density of 1 A g−1.